?EFFECT OF pH ON NI ADSQRPTION IN ORGi\.NO .•MINERAL COMPLEXES (Biological Sciences - PJSIR, 1999)
Adsorption of nickel on four different soils were studied. These were: Gujranwala series, Kotli series, LyallpurseriesandaPacca series.EffectoforganicmatterandpHonnickeladsorptionwerestudied.The pH greatlyinfluencedthecharacteristicsofadsorptionisotherms.KotliseriesH-Claycomplexesadsorbed more Nithan corresponding H-clays atallpHwhilereversewastrueinPaccaseries,Gujranwalaseries andmixed behaviourwasnotedinLyallpurseries.OrganicmattersolubilizationtookplaceatpH>5.0inLyallpurseries.